2012
DOI: 10.1177/0309364612437905
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and barriers to prosthesis users participation in physical activity, exercise and sport

Abstract: Background: The UK will host the Paralympics in 2012 and the Commonwealth Games in 2014 showcasing the talents of elite athletes and aiming to inspire the population to become involved. However, low levels of physical activity are prevalent: only 40% of men and 28% of women meet the minimum UK physical activity recommendations. The population of people with limb absence is no exception. Objectives: To determine if people with amputation are participating in physical activity and sport; whether post-amputation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 24 publications
0
40
0
2
Order By: Relevance
“…Multiple studies in patients with chronic heart failure, or who have experienced a cerebrovascular accident or myocardial infarction, have shown that specialized physical training programs can improve various indices of cardiovascular health (33–35), reduce fatigue (33), and improve physical function and quality-of-life (36, 37). Survivors with musculoskeletal late effects can benefit from working with specialists who have experience with prosthetics and movement retraining to facilitate physical function and improve body image (38). Thus, physical training programs may have important health benefits for survivors who develop chronic illnesses following cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in patients with chronic heart failure, or who have experienced a cerebrovascular accident or myocardial infarction, have shown that specialized physical training programs can improve various indices of cardiovascular health (33–35), reduce fatigue (33), and improve physical function and quality-of-life (36, 37). Survivors with musculoskeletal late effects can benefit from working with specialists who have experience with prosthetics and movement retraining to facilitate physical function and improve body image (38). Thus, physical training programs may have important health benefits for survivors who develop chronic illnesses following cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…14,41,42 This is not unexpected due to the barriers to PA that this population faces, and is also consistent with previously published literature regarding PA in patients with an amputation. [21][22][23][24][29][30][31]36 The finding that female gender, increasing age, and disease burden correlate with decreased PA is also observed in the general population. 41 In addition, a prior study indicated that female patients are less likely to be successfully fitted with a lower-limb prosthesis than male patients, which could contribute to this disparity.…”
Section: Discussionmentioning
confidence: 68%
“…The majority of these studies find that individuals with an amputation have lower PA than recommended. [21][22][23][24][25][26] One study suggests that individuals with an above-knee amputation (AKA) have lower PA than those with a below-knee amputation (BKA). 27 Some note that individuals with a dysvascular amputation etiology have lower PA than those with a nondysvascular etiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a reported paucity of available case studies of sports prostheses design to help inform practitioners [6]. The limited case studies have included prostheses designs for swimming [7], running [8], athletics [9], golf, fishing, baseball and cycling [10] skiing [11], triathlon [12] and snowboarding [13].…”
Section: Athletes and Prosthetics Technologymentioning
confidence: 99%